(untitled) (Journal of Parents and Teachers, 2013)
In the article it is shown the experience of a group of students of third grade of ESO who have done an audiovisual editing. It explains the steps, the preparation and the evaluation of the project. It also includes a time sequence and al the objectives that needed to be achieved.